Impact of hydronephrosis and kidney function on survival in newly diagnosed advanced cervical cancer - Fernanda Bronzon Damian; Fernando Kude de Almeida; Fernando Schmidt Fernandes; Mirela Foresti Jimenez (Gynecologic Oncology Reports, 2022)
Objectives: To assess the impact of hydronephrosis and kidney function in newly diagnosed advanced cervical cancer patients. Methods: A retrospective cohort study of newly diagnosed cervical cancer stage IIIB to IVB was conducted in a tertiary hospital in Brazil. Data from clinical records between 2014 and 2018 were reviewed. Results: A total of 285 women with advanced cervical cancer and no previous cancer treatment were included. 108 (37.9%) patients were diagnosed with hydronephrosis (HN) before or during the first treatment, 49 (17.2%) patients underwent ureteral obstruction relief, and emergency hemodialysis was performed in 17 patients due to uremia. The median overall survival (mOS) was 46.9 months for non-HN, 19.2 months for unilateral-HN, and 10.0 months for bilateral-HN (non-HN vs HN-groups, p = 0.0001). Patients with eGFR >= 60 mL/min/1.73 m2, before or during the first cancer treatment, had mOS of 46.9 months, 23.5 months, and 11.1 months for non-HN, unilateral-HN and bilateral-HN, respectively (non-HN vs bilateral-HN, p = 0.002). Patients with eGFR < 60 mL/min/1.73 m2 had mOS 23.4 months, 19.2 months, and 10.0 months for non-HN, unilateral-HN and bilateral-HN, respectively (non-HN vs bilateral-HN, p = 0.003). In the HN group, mOS was 11.2 months among those who underwent urinary diversion and 15.6 months among those who did not; p = 0.2. On multivariate analysis, cancer treatment, FIGO stage, and HN were prognostic factors for OS; however eGFR < 60 mL/min/1.73 m2 does not appear to be associated with worse survival by itself (p = 0.7). Conclusion: HN seems to have a negative effect on survival of patients with cervical cancer even after adjustment for FIGO stage and cancer treatment. The mOS does not appear to be worse in patients with HN who required urinary diversion compared to those who did not.